Kesadaran metakognitif siswa setelah mengikuti pembelajaran modifikasi cooperative script dipadu Hybrid-PjBl - Nurwidodo Nurwidodo; Dini Fithria Nurul Aisyah; Ahmad Fauzi (JINoP (Jurnal Inovasi Pembelajaran), 2021)
Empowering students’ metacognitive awareness is among the 21st century learning strategies. This research aims to determine the profile of students’ metacognitive awareness in Biology subject through the implementation of Cooperative Script (CS) modification strategy combined with Hybrid-PjBl. It employed quantitative method with the participants of students from XI IPA SMA 5 Malang. The instrument for data collection was Metacognitive Awareness Inventory, with descriptive statistics and Pearson Product Moment as data analysis techniques. Results show that 20% of students’ metacognitive awareness was in the “very good” category; 40% of students in the “good” category; while the remaining 40% were in the “fair” category. Based on more detailed analyses, one component of metacognition is classified as “fair”, six components are classified as “good”, while the rest is classified as “very good”. Most metacognition components are correlated with each other. These findings indicate that Biology learning with CS modification combined with Hybrid-PjBL potentially empowers students’ metacognitive awareness.